Reinforcing the performance of health belief model using health literacy in anticipating adoption of smoking preventive behaviors in university students - Rahman Panahi; Ali Ramezankhani; Mahmoud Tavousi; Aliasghar HaeriMehrizi; Shamsaddin Niknami (Mashhad University of Medical Sciences, 2018)
Background and objective: Health literacy (HL) is associated with the adoption of preventive behaviors and has a potential effect on reinforcing the health belief model (HBM). Due to the increasing prevalence of smoking among university students, this study aimed to determine the role of HL in reinforcing the performance of HBM in anticipating the adoption of smoking preventive behaviors. Methods:This cross-sectional study was carried out among 340 dormitory students of Shahid Beheshti University of Medical Sciences in Tehran, selected by sinle-stage cluster sampling. The data gathering tool was a researcher-made questionnaire based on HBMfor smoking preventive behaviors and HL questionnaire (HELIA). The data were analyzed using Confirmatory Factor Analysis method by Liserl software 8.8 and multiple regression analysiswith SPSS software. Results: The results of the validity of two versions of HBM(original version and combined version with HL) in confirmatory factor analysis showed that fitness indexes of combined version with HL are better. Multiple regression analysisreflected that the coverage ratio of behavior variance of the combined version (r2= 36.5) is more than the original version (r2= 24. 6).   Conclusion: To design and implement educational programs in order to adoption of smoking preventive behaviorsamong students, using HBM combined with HL is more effective than the original version of this model. Paper Type:Research Article.